Medo odontológico da infância à adolescência: análise de caminhos em uma coorte de 10 anos - Godois, Leonardo da Silva (2021)
Oral diseases are an important problem for health on a global scale, showing unequal severity and prevalence within and between countries. Dental fear may influence on children's oral conditions and can influence to avoid regular visits to the dentist, which can represent a considerable problem for both the patient and the dentist. The aim of this study was to explore the pathways that demographic, psychosocial, behavioral and clinical factors can influence dental fear from childhood to adolescence. This cohort study started in 2010, when a random sample of 639 preschoolers (1-5 years) was assessed during the National Children’s Vaccination Day in schoolchildren from Santa Maria, Southern Brazil. The individuals from this sample were reassessed in 2020, totaling 10 years of follow-up with 429 reevaluated adolescents and a 67.13% retention rate. Dental fear was measured in the last assessment, using the Brazilian version of the Children's Fear Survey Schedule-Dental Subscale (CFSS-DS). Demographic, socioeconomic and behavioral factors were evaluated at the baseline and have been also collected in the follow-up through a semi-structured questionnaire. Clinical data were obtained through oral assessments performed by previously trained and calibrated examiners. Statistical analysis was performed using Structural Equation Modeling (SEM) to test the different pathways leading to dental fear in adolescents. Higher levels of untreated dental caries, dental visits for non-routine reasons, and low sense of coherence (SOC) at T2 directly impacted dental fear at T2. Considering the indirect effects, presence of dental caries, low household income, and low maternal education at T1 indirectly impacted higher levels of dental fear over 10 years via dental caries at follow-up. Moreover, the presence of dental caries at T2 had an indirect effect in the outcome, through dental visits for non-routine reasons. Therefore, our results suggest that higher levels of dental fear are directly associated with clinical, psychosocial and behavioral factors. Furthermore, dental fear is indirectly affected by socioeconomic and clinical conditions from early childhood.